Pengembangan Model Pembelajaran Proses Kreatif Berteater - Lela Nurfarida; Herwan Herwan (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
The main problem of learning literature in school and college is the lack of experience and weakness of students' ability in literature. The experience and abilities in the literature include experience of appreciation and expression, both oral and written. Meanwhile, theoretically and the demands of the curriculum, appreciation experience and students' ability in expression are the main goals of literary learning. This is a fundamental problem of literary learning, the gap between the expected with the reality that occurred. One of the skills of literary expression is theatre activities, in which the activities are required to appreciate the high story played. Therefore it is necessary to design the learning process of creative in the theatre world from start creation and appreciation of the script to the show. This research will parse the full picture of the model of literary activities in the world of theatre in the sixth semester students who contracted theatre courses in the Department of Language Education and Indonesian Literature at the Faculty of Teacher Training and Education Untirta through the development method. The output in this research is the product of creative process of theatre in the form of students' work in theatre and long term goal is expected to create qualified human resources in the future.